2011
DOI: 10.1007/s10522-011-9340-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethical aspects of aging research

Abstract: During the last 50-60 years, due to development of medical care and hygienically safe living conditions, the average life span of European citizens has substantially increased, with a rapid growth of the population older than 65 years. This trend places ever-growing medical and economical burden on society, as many of the older subjects suffer from age-related diseases and frailty. Coping with these problems requires not only appropriate medical treatment and social support but also extensive research in many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Investigators rarely discussed these concepts as important issues affecting patient treatment during a dental emergency. Although investigators in some articles addressed issues arising from a conflict of interest between a patient with a medical or cognitive condition and his or her surrogate or proxy, 55,72,74 there were no articles in which the investigators discussed these issues in the geriatric dentistry literature. Overall, in our review we found a paucity of articles discussing the topic of informed consent in geriatric dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…The EOL clinical research literature, particularly in the oncology field, is rich with considerations of ethical conduct of research [ 11 , 12 , 27 , 28 ]. Seppet and colleagues, for example, framed key ethical issues for research with dying individuals, including recruitment considerations for terminally ill participants, establishment of inclusion and exclusion criteria, provisions to ascertain sex and gender differences, assessment of capacity to provide informed consent, protection of privacy, and biobanking issues [ 29 ]. While the notion of EOL clinical research is not in itself ethically problematic, it can be difficult to conduct such research well given the inherent practical and logistical challenges [ 30 , 31 ].…”
Section: Ethical Principles For Clinical Research At the Eolmentioning
confidence: 99%
“…These themes were intermixed with staff members' self-determined responsibility to honor the Last Gift participants' wishes with dignity and respect as well as successfully accomplish their respective tasks. This articulation of personal responsibility is a hallmark of the "provision of high-quality care" [19] at the EOL, as echoed in existing literature that it is of utmost importance to honor patients' wishes and hold dignity and ethics at the forefront of EOL work, which can be emotionally charged in itself [1,[20][21][22][23][24]. Additionally, as EOL and organ donation ethics are evolving and may be subjected to contention [25], the study team must ensure patient autonomy [22], address challenges swiftly, and course correct as necessary [26].…”
Section: Discussionmentioning
confidence: 99%